Factors Participating in Modulating the Mechanisms of Immune Protection of Lungs during Pneumonia - A. N. Mikerov (Проблемы особо опасных инфекций, 2012)
Presented are the modern data about factors modulating the mechanisms of immune protection of lungs during pneumonia. Considered is the role of protein A (SP-A) in provision of lungs resistance to infectious disease. The negative impact on protein A (SP-A) by ozone is shown. Noted is the existence of the gender particularities in pneumonia morbidity and sensitivity to ozone.